Cellular stress increases DRIP production and MHC Class I antigen presentation - Pach, Natalie; Basler, Michael (Frontiers in Immunology, 2024)
Background: Defective ribosomal products (DRiPs) are non-functional proteins rapidly degraded during or after translation being an essential source for MHC class I ligands. DRiPs are characterized to derive from a substantial subset of nascent gene products that degrade more rapidly than their corresponding native retiree pool. So far, mass spectrometry analysis revealed that a large number of HLA class I peptides derive from DRiPs. However, a specific viral DRiP on protein level was not described. In this study, we aimed to characterize and identify DRiPs derived from a viral protein.Methods: Using the nucleoprotein (NP) of the lymphocytic choriomeningitis virus (LCMV) which is conjugated N-terminally to ubiquitin, or the ubiquitin-like modifiers FAT10 or ISG15 the occurrence of DRiPs was studied. The formation and degradation of DRiPs was monitored by western blot with the help of a FLAG tag. Flow cytometry and cytotoxic T cells were used to study antigen presentation.Results: We identified several short lived DRiPs derived from LCMV-NP. Of note, these DRiPs could only be observed when the LCMV-NP was modified with ubiquitin or ubiquitin-like modifiers, but not in the wild type form. Using proteasome inhibitors, we could show that degradation of LCMV-NP derived DRiPs were proteasome dependent. Interestingly, the synthesis of DRiPs could be enhanced when cells were stressed with the help of FCS starvation. An enhanced NP118-126 presentation was observed when the LCMV-NP was modified with ubiquitin or ubiquitin-like modifiers, or under FCS starvation. Conclusion: Taken together, we visualize for the first time DRiPs derived from a viral protein. Furthermore, DRiPs formation, and therefore MHC-I presentation, is enhanced under cellular stress conditions. Our investigations on DRiPs in MHC class I antigen presentation open up new approaches for the development of vaccination strategies.